Sonographic evaluation of congenital cystic neck masses with histopathological correlation (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Accurate diagnosis is important for planning of management of the congenital cystic neck mass. Clinical history, physical examination and appropriate knowledge of embryology and anatomy of the cervical region frequently allow the differential diagnosis to be narrowed and ultrasound especially high frequency ultrasound help to further confirmation. USG has been used as the initial imaging procedure in the evaluation of them. Ultrasound not only confirms the cystic nature of the lesion but also evaluates exact location, size, extent, relation to the surrounding structures and internal characteristic of mass.Objectives: To establish the usefulness of ultrasound in the evaluation of congenital cystic neck masses.Methods: From January 2014 to March 2018 a total 50 patients with clinically suspected congenital cystic mass in the neck region were selected who under want operative treatment and histopathological examination. A through history taking and physical examination were done then patient were scanned with gray scale ultrasound and colour Doppler in necessary case. Histopathological report collected from the patient and compare with USG diagnosis.Results: In USG 37 patient diagnosed as congenital lesions and 13 patient diagnosed as non-congenital lesion. Among the congenital lesions thyroglossal duct cyst-19, branchial cleft cyst-12, cystic hygroma-4, hemangioma-1 and epidermoid cyst-1. In histopathology 32 patient diagnosed as congenital lesion and 18 diagnosed as non-congenital lesion. Among the congenital lesions thyroglossal duct cyst-18, branchial cleft cyst-8, cystic hygroma-4, hemangioma-1 and epidermoid cyst-1. Among the 19 USG diagnosed thyroglossal duct cyst 17 is confirmed by histopathology and 2 is differ. Among the 12 USG diagnosed branchial cleft cyst 7 is confirmed by histopathology and 5 is differ. Over all sensitivity of USG-93.7% and specificity-64% and accuracy-74%.Conclusion: USG is a useful modality for the diagnosis of congenital cystic mass in the cervical region.Bangladesh J Otorhinolaryngol; April 2018; 24(1): 68-78